FACTORS ENDANGERING THE PROFESSIONAL ACTIVITY OF THE EMERGENCY MEDICAL PROFESSIONALS - D. Todorova; A. Andonova (Trakia Journal of Sciences)
The endangering factors from the professional activity of the medical teams working at CEMC to be more comprehensively studied, analyzed and summarized. Preliminary interviews were conducted with medical professionals working at CEMC. On this basis, a questionnaire was developed, surveying through a sociological method the opinion of medical professionals from the Centers for Emergency Medical Care. The implemented structural and organizational changes still do not outline fully clear perspectives ahead of the work of the emergency rooms. These ambiguities suppose the risky nature (endangering factors) of the activity of the emergency medical professionals. In the outlining of the factors endangering the professional activity of the emergency medical professionals who work at the emergency centers the questions of interest are related to: the difficulties that they face during the execution of their professional obligations, the most exhausting components of the work, the workplace aggression and so on. Factors endangering the professional activity of the emergency medics determine their choice of job which on the other hand is a really important factor that determines job satisfaction.